Batam City Culinary Documentary Video Design - Alexander Alexander; Diny Anggraini Adnas (Universitas Internasional Batam, 2024)
The aim of this research is to delves into Batam City's culinary richness, strategically positioned between the Strait of Malacca and the Strait of Singapore. Focusing on a documentary video, the study explores planning and development processes, aiming to uncover Batam's diverse culinary heritage. This culinary documentary video was made using the applied research method. Through interviews and immersive storytelling, it seeks to document unique traditions and food culture. Significantly, the project promotes local cuisine to a broader audience, attracting tourists and supporting local culinary businesses. Serving as a gateway to Batam's gastronomic treasures, it contributes to cultural appreciation and economic development.